2022
DOI: 10.3390/s22072761
|View full text |Cite
|
Sign up to set email alerts
|

Similarity Simulation on the Movement Characteristics of Surrounding Rock and Floor Stress Distribution for Large-Dip Coal Seam

Abstract: The question of how to mine safely in close multi coal seams is the main concern for coal operators, in particular for large-dip coal seams with complex geological and mechanical conditions. This paper presents a detailed similarity simulation on the movement characteristics of the overburden and the stress distribution of underlying strata in terms of a specific coal mine in the Tielieke mining area of the Kubai coalfield via a three-dimensional photogrammetry system and a high-speed static resistance analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…However, there is still a lack of scientific understanding in terms of the structural characteristics of the overlying strata and the distribution of the "three zones" in the abandoned mine area of shallow-buried double or multiple coal seams [22]. Cao [23] performed similar simulations of the overlying strata movement characteristics and the underlying strata stress distribution in the coal mines of the study area, and found that the overlying strata around the coal pillar formed asymmetrically, and that the fault zone was perpendicular to the long wall and the overlying strata can be "M-shaped" only during deep coal mining. Ghabraie [24] studied the subsidence characteristics of multi-coal-seam mining by different similar simulation experiments.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is still a lack of scientific understanding in terms of the structural characteristics of the overlying strata and the distribution of the "three zones" in the abandoned mine area of shallow-buried double or multiple coal seams [22]. Cao [23] performed similar simulations of the overlying strata movement characteristics and the underlying strata stress distribution in the coal mines of the study area, and found that the overlying strata around the coal pillar formed asymmetrically, and that the fault zone was perpendicular to the long wall and the overlying strata can be "M-shaped" only during deep coal mining. Ghabraie [24] studied the subsidence characteristics of multi-coal-seam mining by different similar simulation experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The steeply inclined fully mechanized mining face in Xinqiang Coal Mine is rare in China. The research on the gob-side entry retaining technique in the working face needs to solve key problems, such as reasonable retention of the filling body, filling system and method, and stability of the filling body [42][43][44]. Related research can not only provide guarantees for safe and efficient production under the condition of steeply inclined coal seam, but also enrich and develop the gob-side entry retaining technology.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the mining in the working face, the bottom plate is affected by the mining of the stress redistribution in the surrounding rock, the formation of a nonuniform stress field in the bottom plate of the working face, and the two-way stress ratio of the surrounding rock; these are obvious differences [33]. The two-way stress ratio of the surrounding rock shows obvious differences, and the bottom-pumping lane is arranged in the rock layer of the bottom plate.…”
mentioning
confidence: 99%